The Appeal of Mount Bromo Tourism : Reviewing The Role of Destination Personality on Destination Image - Mehdiviky, Muh. Mughny; Akhrani, Lusy Asa (Graduate School, Universitas Brawijaya, 2024)
The likelihood of an individual leaving home is influenced by their motivation to travel The human desire to change one’s environment serves as a driving force for travel, while the attractiveness of a destination functions as a pull factor that encourages visitation. However, an increasing tendency among destination managers is to focus primarily on physical appearance and facilities, which can result in destinations appearing similar and lacking distinctive characteristics. This study aims to investigate the role of destination personality and its five trait dimensions—excitement, sincerity, sophistication, competence, and ruggedness—in shaping the destination image of Mount Bromo using a quantitative approach. A total of 224 respondents were selected through purposive sampling, with eligibility criteria requiring participants to be at least 17 years old and to have visited Mount Bromo at least twice. Data collected using the Destination Personality Scale were analyzed through multiple linear regression analysis. The results indicate that the five destination personality traits simultaneously influence destination image. Partially, the traits of excitement, sophistication, and ruggedness have a significant role in shaping destination image, while sincerity and competence do not exhibit significant partial effects. These findings provide practical insights for the development and management of Mount Bromo as a tourist destination